Haemato-Biochemical and Clinical Analysis of Dogs with Urinary Tract Infection Associated with Escherichia coli - P. Rana; D.G. Dighe (The Indian Veterinary Journal, 2025)
The study entitled was carried out on dogs suspected for urinary tract infection at Mumbai Veterinary College, Parel. The Mean ± SE of hemoglobin, PCV, and TEC, of dogs with E. coli associated UTI was 2.23±0.62 gm%, 35.96±1.82%, and 5.45±0.28×106/cmm respectively. These parameters were found to be within normal range. Mean ± SE of Neutrophils was 77.89±1.42 %, for Eosinophils 1±0.31%, for Lymphocytes 19.53±1.25%, for Monocytes 1.42±0.18% and for Basophils was 0.16±0.12%. Marked leukocytosis with neutrophilia associated with UTIs was observed. Mean ± SE of ALP, AST and ALT was 108.84±9.77 U/L, 47.33±4.44 U/L and 50.24±9.85 U/L respectively. These values were almost normal. Mean ± SE of total protein, albumin and globulin were 6.42±0.2 g/dl, 2.52±0.1 g/dl and 3.86±0.24 g/dl respectively. There was mild hypoalbuminemia with hyperglobulinemia. Mean ± SE of BUN was 30.41±5.85mg/dl and mean ± SE of creatinine was 1.72±0.21. This elevation may be due to decrease renal filtration due to the renal injury caused by inflammation and infection.